2017
DOI: 10.1002/acp.3349
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐admonition Suggestion in Live Showups: When Witnesses Learn that the Cops Caught ‘the’ Guy

Abstract: Participants (N = 189) witnessed the theft of a computer and were immersed into what they were led to believe was an actual police investigation that culminated in a live showup. After the crime, an officer responded to the scene to take witness statements. Minutes after his arrival, the officer received a radio dispatch that could be heard clearly by the witnesses. The dispatch either stated that the Sherriff had '…caught the guy…' or '…detained a suspect who matched the thief 's description…' and instructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…This is typical of the proportion of doubters found in previous field-simulation experiments that have employed a similar paradigm (Eisen, Skerrit-Perta, et al, 2017; Eisen, Smith, et al, 2017). Previous field-simulation experiments have found that participants who did not express significant doubts that the crime and identification procedures were real (henceforward, “true believers”) were significantly more likely to positively identify the suspect presented to them at a show up (Eisen, Skerrit-Perta, et al, 2017; Eisen, Smith, et al, 2017). This finding was replicated in the present study: True believers were significantly more likely than doubters to make suspect identifications when show ups were used, χ 2 (1, 382) = 8.76, p < .01.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…This is typical of the proportion of doubters found in previous field-simulation experiments that have employed a similar paradigm (Eisen, Skerrit-Perta, et al, 2017; Eisen, Smith, et al, 2017). Previous field-simulation experiments have found that participants who did not express significant doubts that the crime and identification procedures were real (henceforward, “true believers”) were significantly more likely to positively identify the suspect presented to them at a show up (Eisen, Skerrit-Perta, et al, 2017; Eisen, Smith, et al, 2017). This finding was replicated in the present study: True believers were significantly more likely than doubters to make suspect identifications when show ups were used, χ 2 (1, 382) = 8.76, p < .01.…”
Section: Methodssupporting
confidence: 65%
“…This experiment compared identifications made when using show ups and lineups under field versus lab conditions. This was accomplished using the field-simulation paradigm (Eisen, Skerrit-Perta, et al, 2017; Eisen, Smith, et al, 2017). Participants witnessed what they were led to believe was an actual theft of a laptop computer.…”
Section: Show Ups Versus Lineupsmentioning
confidence: 99%
“…Because showups are conducted in the field during which search-and-detain operations are actively unfolding, care should be taken to ensure that witnesses do not overhear police radio conversations that could prejudice a showup procedure. In an experiment using a high-realism paradigm for studying showup identifications, overhearing the suggestion that the sheriff had caught the guy significantly increased false identifications from showups but did not affect accurate culprit identifications (Eisen, Skerrit-Perta, Jones, Owen, & Cedre, 2017).…”
Section: Reducing the Suggestiveness Of Showupsmentioning
confidence: 99%
“…Witnesses can be influenced during their interactions with police before the video recorder is even turned on during a lineup procedure. Eisen et al (2017) conducted a field simulation experiment in which witnesses overheard officer communications prior to the identification procedure that "they caught the guy." This comment increased response latency (time viewing the suspect) and increased false identifications.…”
Section: Administrator Behaviormentioning
confidence: 99%